How an intrinsically disordered regulatory subunit assembles a PP1:eIF2 complex - Alexander C. Jones; Jian Wu; Susan S. Taylor (Cell Reports, 2024)
Fatalska et al.1 use an interdisciplinary strategy to elucidate how an intrinsically disordered regulatory subunit of protein phosphatase 1 binds trimeric eIF2 and positions the phosphatase-substrate complex for dephosphorylation. As validation, they show that a disease mutation abolishes the interaction.